2018
DOI: 10.1038/s41598-018-25569-4
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids and their respective conjugates elicit different responses in neonatal cardiomyocytes: role of Gi protein, muscarinic receptors and TGR5

Abstract: Bile acids are recognised as bioactive signalling molecules. While they are known to influence arrhythmia susceptibility in cholestasis, there is limited knowledge about the underlying mechanisms. To delineate mechanisms underlying fetal heart rhythm disturbances in cholestatic pregnancy, we used FRET microscopy to monitor cAMP release and contraction measurements in isolated rodent neonatal cardiomyocytes. The unconjugated bile acids CDCA, DCA and UDCA and, to a lesser extent, CA were found to be relatively p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…Recently, BAs have been recognized as signaling molecules that can integrate with their receptors, including the nuclear Farnesoid X Receptor (FXR) and Bile Acid G‐Protein‐Coupled Membrane Receptor (TGR5). TGR5 is known to be expressed by multiple organ systems such as the liver, the renal system, brain, heart and the retinas . The roles for TGR5 in regulating metabolic homeostasis have been well documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, BAs have been recognized as signaling molecules that can integrate with their receptors, including the nuclear Farnesoid X Receptor (FXR) and Bile Acid G‐Protein‐Coupled Membrane Receptor (TGR5). TGR5 is known to be expressed by multiple organ systems such as the liver, the renal system, brain, heart and the retinas . The roles for TGR5 in regulating metabolic homeostasis have been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…TGR5 is known to be expressed by multiple organ systems such as the liver, the renal system, brain, heart and the retinas. [8][9][10][11][12] The roles for TGR5 in regulating metabolic homeostasis have been well documented. In the last several years, research on BAs and their receptors has been extended to their possible roles on the regulation of endothelium functions.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13]22,23 On rat models and in in vitro studies, it has been shown that TBAs, especially taurocholic acids, can cause sinoatrial node dysfunction, desynchronized cardiomyocyte contraction, and alteration in atrioventricular conduction system due to changes in calcium dynamics. 11,12,[24][25][26][27][28] Also, Ibrahim et al demonstrated that bile acids can play a role as partial agonists of muscarinic receptor type 2 and lead to reducing the contraction rate of neonatal cardiomyocytes. 27 Considering the data obtained, it is suggested that ICP-associated fetal arrhythmia and IUFD can be the results of the accumulation of elevated bile acids in fetal cardiac cells.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,[24][25][26][27][28] Also, Ibrahim et al demonstrated that bile acids can play a role as partial agonists of muscarinic receptor type 2 and lead to reducing the contraction rate of neonatal cardiomyocytes. 27 Considering the data obtained, it is suggested that ICP-associated fetal arrhythmia and IUFD can be the results of the accumulation of elevated bile acids in fetal cardiac cells. Accordingly, in this study, ICP groups were divided into two sections, mild and severe ICP, with reference to bile acid levels, and the data showed that fetal mechanical PR interval was longer in the severe ICP group than in the mild ICP group (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Those effects were mediated by M2 muscarinic receptor [41]. Similarly, Ibrahim et al [42] showed that conjugated bile acids action was mediated by M2 muscarinic receptor and not sphingosine 1 phosphate 2 receptor.…”
Section: Muscarinic Receptormentioning
confidence: 94%